Comparative study of methodologies for SOH diagnosis and forecast of LFP and NMC lithium batteries used in electric vehicles (2024)
ABSTRACT: The exponential growth of electric mobility requires alternatives to extend the life of batteries in new applica tions and reduce the environmental impact of retired lithium batteries. The second life is an economic and environment-friendly alternative for battery management. The development of fast, low-cost, and reliable diagnostic methodologies makes it possible to increase the economic benefits and reduce the remanufacturing time of second-life batteries (SLBs). In the present work, battery state of health (SOH) distribution analysis, incremental capacity (IC), internal resistance (IR), and electrochemical impedance spectroscopy (EIS) were applied as diagnostic methodologies for two different chemistries of lithium-ion batteries previously used in electric vehicles (EV). In addition, module equalization in batteries was done in order to assess whether the state of module charge (SOC) variation affects the SOH. The results demonstrate that the diagnosis methodology depends on the chemistry of the battery, and that there is no single reliable diagnostic procedure that can be applied to all types of lithium-ion batteries. It was determined that the most adequate diagnostic method for LFP batteries (LiFePO4 cathode) is the IC method, while for NMC batteries (LiNi0.33Mn0.33Co0.33O2 cathode) the IR and EIS diagnostic methods are the most appropriate. Similarly, the present work proposed a simple method ology for IC capacity diagnosis and a general expression for SOH determination by IC and incremental voltage diagnosis of LFP batteries. Higher stability of LFP respect to NMC modules was observed during the SLBs per formance, retaining >99 % after 500 cycles for LFP, compared with 90.2 % for NMC. The remaining useful life (RUL) shows that there are kinetics and lithium inventory changes in the batteries temperature-dependent.